Structural, Electrical, Ferroelastic Behavior, and Multiferroic Properties of bifeo3 - Casagrande-Denardin, J (Springer, 2020)
BiFeO3 was synthesized by conventional solid-state reaction method, and its structural, vibrational, electrical, ferroelastic, and multiferroic properties were studied. X-ray diffraction analysis and Rietveld refinement confirmed its rhombohedral crystal structural with the space group of R3c. SEM images show the rectangular shaped micrograins. The stress–strain curves obtained from uniaxial compressive tests with different maximum stresses exhibit hysteresis loops with different remnant strains due to ferroelastic domain switching during compression loading and partial domain switching back upon unloading. From Raman spectra, we have observed 3A1 and 6E modes in the range of 100–600 cm−1. Dielectric constant and dielectric loss were measured as a function of frequency in the range 100 Hz to 1 MHz. The leakage current density was found to be 8.07 × 10 - 7 A/cm2 at higher electric field. In further, we performed the ferroelectric, magnetic, and magnetoelectric effect for the confirmation of its multiferroic behavior. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.